Visuospatial working memory of abacus trained and untrained children - Evangeline Efe Ansah; Nana Yaa Nyarko; David Kwame Kumador; Justice Owusu-Bempah; Sheriffa Mahama (PLoS ONE, 2025)
Background This research investigated whether there was a significant change in the visuospatial working memory of children who underwent abacus training. Method A quasi-experimental research design with a quantitative approach was employed for the study. Ninety (90) children were recruited as the experimental group and one hundred (100) children as the control group. The experimental group participated in abacus training as part of their extracurricular activities at school. A questionnaire assessing visuospatial memory was administered to both groups before and after the training. Findings The findings revealed a significant change in the mean scores of the experimental group from before and after the abacus training (p < .01) compared to the control group. This signified that abacus training may potentially lead to significant improvement in visuospatial working memory. Conclusion It is suggested that future research be conducted using a longitudinal approach to enable a more comprehensive assessment of the full course of abacus training.